Desensitization of the Platelet Aggregation Response to ADP: Differential Down-regulation of the P2Y1 and P2cyc Receptors - Baurand, Anthony; Eckly, Anita; Bari, Nadège; Léon, Catherine; Hechler, Béatrice; Cazenave, Jean-Pierre; Gachet, Christian (Thrombosis and Haemostasis, 2000)
Platelets activated by ADP become refractory to restimulation, but the mechanism of this process is not well understood. A normal platelet response to ADP requires coactivation of the P2Y1 receptor responsible for shape change and the P2cyc receptor, responsible for completion and amplification of the response. The aim of the present study was to characterize the desensitization of platelets to ADP and to determine whether or not these two receptors are desensitized simultaneously through identical pathways when platelets become refractory to ADP. It was found that full inhibition of platelet aggregation in response to restimulation by ADP required the presence of ADP in the medium or use of a high concentration (1 mM) of its non-hydrolysable analogue ADP β S. Platelets incubated for 1 h at 37° C with 1 mM ADP β S and resuspended in Tyrode’s buffer containing apyrase displayed a stable refractory state characterized by the inability to aggregate or change shape in response to ADP. ADP β S treated platelets loaded with fura2/AM showed complete blockade of the calcium signal in response to ADP, whereas the capacity of ADP to inhibit PGE1 stimulated cAMP accumulation in these platelets was only diminished. Consequently, serotonin was able to promote ADP induced aggregation through activation of the Gq coupled 5HT2A receptor while adrenaline had no such effect. These results suggested that the refractory state of ADP β S treated platelets was entirely due to desensitization of the P2Y1 receptor, the P2cyc receptor remaining functional. Binding studies were performed to determine whether the P2Y1 and/or P2cyc binding sites were modified in refractory platelets. Using selective P2Y1 and P2cyc antagonists (A3P5P and AR-C66096 respectively), we could demonstrate that the decrease in [33P]2MeSADP binding sites on refractory platelets corresponded to disappearance of the P2Y1 sites with no change in the number of P2cyc sites, suggesting internalization of the P2Y1 receptor. This was confirmed by flow cytometric analysis of Jurkat cells expressing an epitope-tagged P2Y1 receptor, where ADP β S treatment resulted in complete loss of the receptor from the cell surface. We conclude that the P2Y1 and P2cyc receptors are differently regulated during platelet activation.
Keywords: Purinergic receptors; refractoriness; ADP; platelet aggregation